Organizational behavior : improving performance and commitment in the workplace - Colquitt, Jason A.; LePine, Jeffery A.; Wesson, Michael J. (McGraw-Hill/Irwin, 2013)
Offers an approach to teaching organizational behavior. This title illustrates how individual, team, leader, and organizational factors shape employee attitudes, and how those attitudes impact performance and commitment